EVALUATION OF THE GRADUAL MASS LOSS OF DIFFERENT NICKEL-TITANIUM INSTRUMENTS AFTER REPEATED USE IN SIMULATED CANALS (CIPEEX, 2025)
To evaluate the gradual loss of mass of different nickel-titanium (NiTi) instruments after repeated use in simulated canals. Four different instrument systems were used: Group 1. Protaper Ultimate®; Group 2. Trunatomy®; Group 3. Wave One Gold® and Group 4. Reciproc Blue®. Each instrument in each group was initially weighed on a high-precision digital analytical scale to obtain the initial weight (PI). Each group will perform the instrumentation of five simulated canals with the aid of the X-Smart Plus® electric motor, following each manufacturer's sequence. After this step, a new weighing was performed to obtain the final weight (PF). The gradual loss of mass of each instrument was calculated by the difference between the PI and PF measurements of each instrument. After obtaining the results, a statistical analysis was performed. Having verified the normality of the sample, an analysis of variance (P < 0.05) was performed. The Tukey test was then used for multiple comparisons between groups.
Keywords: root canal preparation; dental instruments; kinematics